The implications of E-cigarettes or "vaping"on the nutritional status - Labban, Louay; Thallaj, Nasser; Malek, Zeina (Jour Med Resh and Health Sci, 2019)
Cigarette smoking is the leading cause of disease and early death all over the world. Even though cigarette smoking has slowly declined in some countries in the world but many alternatives have gained popularity. Many people may turn to e-cigarettes as a way to try to stop smoking, and there is evidence that they can be effective for smoking cessation. Even so, E-cigarettes would never be considered the first choice for smoking cessation because of the risks and given the extent of the current outbreak of severe lung disease, e-cigarettes should be avoided at the present time. The FDA has not approved e-cigarettes as a way to quit smoking. Doctors and the FDA recommend evidence-based methods for quitting smoking. If you have used e-cigarettes to stop smoking, do not return to smoking cigarettes instead of using e-cigarettes. Instead, turn to safe ways to deliver nicotine such as nicotine patches, gum, lozenges, and nasal spray. Research works are still limited on the effect of E-smoking on the nutritional health. However, products included in the vape can cause so many nutritional problems which affect the health status in general such as vomiting and diarrhea lead to electrolytes imbalance and dehydration, loss of appetitie and malabsorption of certain minerals such as Ca, Fe and Mg and some vitamins such as Vitamin C and D.